Cheating amongst youth offenders: How peers and their social status influence cheating. - Leong, Kaiwen; Li, Huailu; Zuo, Sharon Xuejing (Economic Inquiry, 2024)
We conducted an experiment with 204 youth inmates to study how the intrinsic psychological cost of cheating that was shaped by peers changed inmates' cheating behavior. We find that innately dishonest inmates who naively revealed their higher willingness to cheat indeed cheated more in the actual game. When given the chance to observe an imperfect signal of whether a peer cheated, only innately dishonest inmates followed this signal and cheated more. This positive treatment effect increases with the saliency of the signal, and becomes more pronounced when the cheating signal is from an influential peer.